When trauma comes to school: Toward a socially just trauma-informed praxis - Catriona O'Toole (International Journal of School Social Work, 2022)
Given the prevalence and devastating consequences of childhood trauma, there has been a surge in initiatives to help schools become trauma-informed. However, despite the growing adoption of such initiatives, a number of concerns have been expressed. These include the lack of attention paid to issues of power and inequality including poverty, racism, and community violence as well as the power of adults to neglect, mistreat or abuse children. Contemporary approaches can also serve to inscribe deficit-based perceptions of children, reinforcing negative stereotypes and stigmas; and they tend to overlook the possibility that schools themselves can contribute to students’ distress, especially in the context of accountability and target-driven agendas. This paper examines current terminology in relation to adversity, trauma, and trauma-informed practice. It shows how current approaches are entangled with a dominant medical model, which views emotional distress as symptoms of mental disorder, rather than as reasonable and intelligible strategies to ensure survival. An alternative approach, co-authored by psychologists and service users/survivors and published by the British Psychological Society, known as the Power Threat Meaning Framework (PTMF) is then discussed. The PTMF is an approach for understanding emotional and psychological distress and troubled or troubling behavior, based primarily on issues of power and inequality. It was chosen in order to forefront social justice concerns, whilst remaining attentive to state-of-the-art and evidence-based understandings of psychological trauma and trauma-informed care. Furthermore, by drawing on the anti-oppression educational theory of Paulo Freire, it is argued a trauma-informed praxis guided and informed by the PTMF, can help redress many of the criticisms of existing approaches in schools.
Keywords: ACEs; trauma; power; inequality; education; liberation